2012
DOI: 10.4155/fmc.11.195
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Glycopeptide Analgesics Derived from Endogenous Enkephalins and Endorphins

Abstract: Over the past two decades, potent and selective analgesics have been developed from endogenous opioid peptides. Glycosylation provides an important means of modulating interaction with biological membranes, which greatly affects the pharmacodynamics and pharmacokinetics of the resulting glycopeptide analogues. Furthermore, manipulation of the membrane affinity allows penetration of cellular barriers that block efficient drug distribution, including the blood–brain barrier. Extremely potent and selective opiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
49
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 97 publications
3
49
0
3
Order By: Relevance
“…A possible reason is that the increased hydrophilicity of the disaccharide shifts the residency of glycopeptide 11L into the aqueous compartment, resulting in faster elimination. 9,29 In summary, we suggest that a flexible linker such as GABA and a helical address segment enhances delivery of the opioid message to neurons within the CNS. Opioid selectivity is determined mainly by the identity of the message after icv administration, but the address segment and linker become more important for delivery after peripheral iv administration.…”
Section: ■ Conclusionmentioning
confidence: 97%
“…A possible reason is that the increased hydrophilicity of the disaccharide shifts the residency of glycopeptide 11L into the aqueous compartment, resulting in faster elimination. 9,29 In summary, we suggest that a flexible linker such as GABA and a helical address segment enhances delivery of the opioid message to neurons within the CNS. Opioid selectivity is determined mainly by the identity of the message after icv administration, but the address segment and linker become more important for delivery after peripheral iv administration.…”
Section: ■ Conclusionmentioning
confidence: 97%
“…In the opioid peptide field, glycosylation has been used as a method to increase enzymatic stability 2,3 and to improve the analgesic profile of several opioid peptides. 4 …”
mentioning
confidence: 99%
“…7,8 The in vitro pharmacological evaluation of these peptides revealed that bioactivity was dependent on the linker type, the identity of the sugar unit, and the position of conjugation. 4 With respect to the anchorage site and on the basis of previous research, two different conjugation positions were considered in this work. In the past, numerous glycosylations have been carried out on the enkephalin sequences.…”
mentioning
confidence: 99%
See 2 more Smart Citations